STRATEGI DAKWAH DALAM MENINGKATKAN JUMLAH FOLLOWERS DI INSTAGRAM (STUDI PADA AKUN @AL.FIRQOTUN.NAJIYAH) - Bahroyni, Al (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study was to determine the da'wah strategy of the al.firqotun.najiyah Instagram account in increasing the number of followers. This type of research is descriptive qualitative research through content analysis approach. Data collection techniques were carried out descriptively. The theory used in this research is use and gratification theory. From the results of this study, it can be concluded that the da'wah strategy for the Instagram account al.firqotun.najiyah in increasing the number of followers varies, including the study of Ustadz Ariful Bahri's live streaming in Medina, AFN Kids and Children's Health content, Ariful motion graphics videos, teaser videos or videos. short, content with viral discussions, and unique and interesting visuals. However, from the many strategies used by the Instagram account al.firqotun.najiyah in increasing the number of followers, the sentimental strategy is the strategy of studying Ustadz Bahri's live streaming, because this study is included in the theory of sentimental strategy in which da'wah focuses on aspects of the heart and moves feelings and hearts. mad'u who are preached